Hubungan Dukungan Keluarga dan Tingkat Harapan Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis - Sulistianingrum, Ratih; Yulanda, Nita Arisanti; Mita, Mita; Maulana, Muhammad Ali; Budiharto, Ichsan (Universitas Malahayati, 2023)
ABSTRACT Chronic Kidney Disease (CKD) is an irreversible and progressive disorder of kidney structure or function. CKD is the biggest reason patients have to undergo hemodialysis. The hemodialysis that is undertaken makes the patient feel hopeless and lose hope. The strongest hope is formed by involving the family. To analyze the relationship between family support and the hope level of chronic kidney disease patients undergoing hemodialysis. This research is a quantitative study with a correlational study design and a cross-sectional approach. Determination of the sample using accidental sampling with 73 respondents. The analysis in this study uses Kendall's Tau test. Characteristics of respondents are dominated by men (60,3%) with an age range of 15–64 (94,5%) years, and most have undergone hemodialysis for 1–5 years (67,1%). The majority of respondents are in the categories of good family support (69,9%) and high hope level (97,3%). Based on the results of Kendall's Tau correlation test, the p-value is 0.037 and the r is 0.246. The results showed that there was a relationship between family support and the hope level of chronic kidney disease patients undergoing hemodialysis. The correlation coefficient value indicates that the two variables have a weak positive relationship. Keywords: Family Support, Level of Hope, Hemodialysis ABSTRAK Penyakit Ginjal Kronis (PGK) merupakan kelainan struktur atau fungsi ginjal yang ireversibel dan progresif. PGK menjadi penyebab terbesar pasien harus menjalani hemodialisis. Hemodialisis yang dijalani membuat pasien merasa putus asa dan kehilangan harapan. Harapan terkuat terbentuk dengan melibatkan keluarga. Menganalisis hubungan dukungan keluarga dan tingkat harapan pasien penyakit ginjal kronis yang menjalani hemodialisis. Penelitian ini merupakan studi kuantitatif desain studi korelasional dan pendekatan cross sectional. Penentuan sampel menggunakan accidental sampling dengan 73 responden. Analisis dalam penelitian ini menggunakan uji Kendall’s Tau. Karakteristik responden didominasi oleh laki-laki (60,3%) dengan rentang usia 15-64 tahun (94,5%) dan sebagian besar telah menjalani hemodialisis selama 1-5 tahun (67,1%). Mayoritas responden berada pada kategori dukungan keluarga baik (69,9%) dan tingkat harapan tinggi (97,3%). Berdasarkan hasil uji korelasi Kendall’s Tau diperoleh p-value 0.037 dan r 0,246. Hasil penelitian menunjukkan adanya hubungan keluarga dan tingkat harapan pasien penyakit ginjal kronis yang menjalani hemodialisis. Nilai koefisien korelasi menunjukkan bahwa kedua variabel tersebut memiliki hubungan positif yang lemah. Kata Kunci: Dukungan Keluarga, Tingkat Harapan, Hemodialisis